RREPS-13. Radiation from Relativistic Electrons in Periodic Structures and Meghri-13. Electron, Positron, Neutron and X-ray Scattering under External Influences: X International Symposium and III International Conference, 23-28 September, 2013, Lake Sevan, Armenia (Tomsk, TPU Publishing House, 2013)
Title screen.